2012
DOI: 10.1039/c2cp41823a
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic character of charge transport parameters in disordered organic semiconductor field-effect transistors

Abstract: In this perspective article, we discuss the dynamic instability of charge carrier transport in a range of popular organic semiconductors. We observe that in many cases field-effect mobility, an important parameter used to characterize the performance of organic field-effect transistors (OFETs), strongly depends on the rate of the gate voltage sweep during the measurement. Some molecular systems are so dynamic that their nominal mobility can vary by more than one order of magnitude, depending on how fast the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 58 publications
(122 reference statements)
1
28
1
Order By: Relevance
“…The gate‐voltage sweep‐rate dependence of the nominal mobility of our devices has also been investigated in order to avoid any over‐estimation of the extracted values. Chen et al have recently reported the influence of the gate‐voltage sweep‐rate in the case of trap dominated FETs exhibiting a dispersive transport . Our devices do not show any significant variation of the extracted mobility for gate‐voltage sweeping rates ranging from 0.5 to 19 V s −1 (see Figure S9, Supporting Information), confirming the good charge transport performances of ditBu‐BTBT .…”
supporting
confidence: 81%
“…The gate‐voltage sweep‐rate dependence of the nominal mobility of our devices has also been investigated in order to avoid any over‐estimation of the extracted values. Chen et al have recently reported the influence of the gate‐voltage sweep‐rate in the case of trap dominated FETs exhibiting a dispersive transport . Our devices do not show any significant variation of the extracted mobility for gate‐voltage sweeping rates ranging from 0.5 to 19 V s −1 (see Figure S9, Supporting Information), confirming the good charge transport performances of ditBu‐BTBT .…”
supporting
confidence: 81%
“…The P(NDI2OD-T2) FETs exhibited an insignifi cant V GS sweep rate dependence for both face-on and edge-on orientations (see Figure S3 in the Supporting Information). According to the dispersive transport model , [ 36,44 ] OFETs prepared with Edgeon P(NDI2OD-T2) should have shown more signifi cant V GS sweep rate dependence than that of Face-on P(NDI2OD-T2). The measured results, however, were similar for both cases.…”
Section: Resultsmentioning
confidence: 99%
“…C8‐BTBT and C 60 were used to grow single‐crystalline p‐n junctions. C 60 is a typical electron transporting material with mobilities as high as 11 cm 2 V −1 s −1 , while C8‐BTBT is among the best hole transporting organic materials . Before growing crystals from their mixed solution, we examined crystallization from solutions with only one component (either C8‐BTBT or C 60 ).…”
mentioning
confidence: 82%